Micromorphological evidence for the role of pressurised water in the formation of large-scale thrust-block moraines in Melasveit, western Iceland - Sigfúsdóttir, Thorbjörg; Phillips, Emrys; Benediktsson, Ívar Örn (Quaternary Research, 2020)
Pressurised meltwater has a major impact on ice dynamics, as well as on sedimentary and deformational processes occurring below/in front of glaciers and ice sheets, but its role in glaciotectonic processes is yet to be fully understood. This study explores micro- and macroscale structures developed within décollements in two thrust-block moraines of Late Weichselian age in Melasveit, western Iceland. The aim is to investigate how pressurised subglacial meltwater can aid the dislocation and transport of large, unfrozen and unlithified sediment blocks by glaciers. A detailed model is constructed for the development of the thrust-block moraines and the microscale processes occurring along their detachments during thrusting. The detachments are characterized by relatively thin zones of crosscutting hydrofractures, which reflect fluctuating water pressures during glaciotectonism. Little evidence of shearing is observed along the leading edges of the thrusts in both moraines. This is supported by high water pressures along the detachments and indicates that the thrust blocks were initially decoupled from the underlying deposits. As the thrust moraines evolved, an increased amount of shear occurred in between events of sediment liquefaction, hydrofracturing, and fluid escape. This was followed by progressive locking up of the detachments and eventual cessation in the accretion of the thrust blocks.